2018
DOI: 10.1186/s13661-018-1071-2
|View full text |Cite
|
Sign up to set email alerts
|

On a p ( x ) $p(x)$ -biharmonic problem with Navier boundary condition

Abstract: In this paper, we study a p(x)-biharmonic equation with Navier boundary condition 2inf x∈ a(x) = a -> 0. By variational methods, we establish the results of existence and non-existence of solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 29 publications
1
28
0
2
Order By: Relevance
“…In 2014, the Liang group reported the ipso vinylation/ortho alkylation using N-tosylhydrazones as the nucleophile (Scheme 38). 86 The base employed was important, as it was needed for both the C-H metalation and diazo species generation steps. During Liang's study, Cs 2 CO 3 was found to be more effective than LiO t Bu.…”
Section: Ortho Alkylation Of Aryl Iodidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, the Liang group reported the ipso vinylation/ortho alkylation using N-tosylhydrazones as the nucleophile (Scheme 38). 86 The base employed was important, as it was needed for both the C-H metalation and diazo species generation steps. During Liang's study, Cs 2 CO 3 was found to be more effective than LiO t Bu.…”
Section: Ortho Alkylation Of Aryl Iodidesmentioning
confidence: 99%
“…Interestingly, if the termination nucleophile is attached to the aryl halide, fused tricyclic structures could be formed (84b). 123 Besides ipso Heck coupling, ipso cyanation 83 and vinylation via carbene insertion 86,124 have been established with aryl iodides and bromides under the intramolecular type-C reaction mode. Recently, the Liang group utilized a Pd/Cu cocatalyst system to synthesize polyfluoroarene-substituted benzofuran and benzopyran derivatives, 125 where a polyflouoroaryl copper species was believed to be the key intermediate.…”
Section: Intramolecular Couplingsmentioning
confidence: 99%
“…As of April 21 st , 2020, a total of 2,395,822 confirmed cases have been reported in 200 countries/territories/areas around the world. reading frame (ORF) proteins [1,2]. In this study, we developed a magnetic chemiluminescence enzyme immunoassay (MCLIA), which showed high specificity and sensitivity in detecting serum immunoglobulin G (IgG) and IgM against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…According to World Health Organization (WHO) as of June 27 th 2020, there has been about 10 million confirmed cases and approaching 500,000 deaths due to coronavirus in the world. [1][2] Much of the human population including the United States of America were under lockdown or official stay-at-home orders to minimize the continued spread of the virus.…”
Section: Introductionmentioning
confidence: 99%